NEW
New Website Launch
Experience the best way to solve previous year questions with mock tests (very detailed analysis), bookmark your favourite questions, practice etc...
1

JEE Advanced 2015 Paper 1 Offline

MCQ (More than One Correct Answer)

Let $$f(x) = \sin \left( {{\pi \over 6}\sin \left( {{\pi \over 2}\sin x} \right)} \right)$$ for all $$x \in R$$ and g(x) = $${{\pi \over 2}\sin x}$$ for all x$$\in$$R. Let $$(f \circ g)(x)$$ denote f(g(x)) and $$(g \circ f)(x)$$ denote g(f(x)). Then which of the following is/are true?

A
Range of f is $$\left[ { - {1 \over 2},{1 \over 2}} \right]$$.
B
Range of f $$\circ$$ g is $$\left[ { - {1 \over 2},{1 \over 2}} \right]$$.
C
$$\mathop {\lim }\limits_{x \to 0} {{f(x)} \over {g(x)}} = {\pi \over 6}$$.
D
There is an x$$\in$$R such that (g $$\circ$$ f)(x) = 1.

Explanation

(a) $$f(x) = \sin \left[ {{\pi \over 6}\sin \left( {{\pi \over 2}\sin x} \right)} \right],\,x \in R$$

$$ = \sin \left( {{\pi \over 6}\sin \theta } \right),\,\theta \in \left[ { - {\pi \over 2},{\pi \over 2}} \right]$$,

where, $$\theta = {\pi \over 2}\sin x$$

$$ = \sin \alpha ,\alpha \in \left[ { - {\pi \over 6},{\pi \over 6}} \right]$$,

where, $$\alpha = {\pi \over 6}\sin \theta $$

$$\therefore$$ $$f(x) \in \left[ { - {1 \over 2},{1 \over 2}} \right]$$

Hence, range of $$f(x) \in \left[ { - {1 \over 2},{1 \over 2}} \right]$$

So, option (a) is correct.

(b) $$f\{ g(x)\} = f(t),t \in \left[ { - {\pi \over 2},{\pi \over 2}} \right]$$

$$ \Rightarrow f(t) \in \left[ { - {1 \over 2},{1 \over 2}} \right]$$

$$\therefore$$ Option (b) is correct.

(c) $$\mathop {\lim }\limits_{x \to 0} {{f(x)} \over {g(x)}}$$

$$ = \mathop {\lim }\limits_{x \to 0} {{\sin \left[ {{\pi \over 6}\sin \left( {{\pi \over 2}\sin x} \right)} \right]} \over {{\pi \over 2}(\sin x)}}$$

$$ = \mathop {\lim }\limits_{x \to 0} {{\sin \left[ {{\pi \over 6}\sin \left( {{\pi \over 2}\sin x} \right)} \right]} \over {{\pi \over 6}\sin \left( {{\pi \over 2}\sin x} \right)}}\,.\,{{{\pi \over 6}\sin \left( {{\pi \over 2}\sin x} \right)} \over {\left( {{\pi \over 2}\sin x} \right)}}$$

$$ = 1 \times {\pi \over 6} \times 1 = {\pi \over 6}$$

$$\therefore$$ Option (c) is correct.

(d) $$g\{ f(x)\} = 1$$

$$ \Rightarrow {\pi \over 2}\sin \{ f(x)\} = 1$$

$$ \Rightarrow \sin \{ f(x)\} = {2 \over \pi }$$ ..... (i)

But, $$f(x) \in \left[ { - {1 \over 2},{1 \over 2}} \right] \subset \left[ { - {\pi \over 6},{\pi \over 6}} \right]$$

$$\therefore$$ $$\sin \{ f(x)\} \in \left[ { - {1 \over 2},{1 \over 2}} \right]$$ ..... (ii)

$$ \Rightarrow \sin \{ f(x)\} \ne {2 \over \pi }$$, [from Eqs. (i) and (ii)]

i.e. No solution.

$$\therefore$$ Option (d) is not correct.

2

JEE Advanced 2014 Paper 1 Offline

MCQ (More than One Correct Answer)
Let $$f:\left( { - {\pi \over 2},{\pi \over 2}} \right) \to R$$ be given by $$f(x) = {[\log (\sec x + \tan x)]^3}$$. Then,
A
f(x) is an odd function
B
f(x) is a one-one function
C
f(x) is an onto function
D
f(x) is an even function

Explanation

$$f:\left( { - {\pi \over 2},{\pi \over 2}} \right) \to R$$

$$f(x) = {[\log (\sec x + \tan x)]^3}$$

$$f( - x) = {[\log (\sec x - \tan x)]^3}$$

$$ = {\left[ {\log \left( {{{(\sec x - \tan x)(\sec x + \tan x)} \over {\sec x + \tan x}}} \right)} \right]^3}$$

$$ = {\left[ {\log \left( {{1 \over {\sec x + \tan x}}} \right)} \right]^3} = {[ - \log (\sec x + \tan x)]^3}$$

$$ = - {[\log (\sec x + \tan x)]^3} = - f(x)$$

$$\therefore$$ f is an odd function. (a) is correct and (d) is not correct.

Also,

$$f'(x) = 3{[\log (\sec x + \tan x)]^2}\,.\,{{\sec x\tan x + {{\sec }^2}x} \over {\sec x + \tan x}}$$

$$ = 3\sec x{[\log (\sec x + \tan x)]^2} > 0\,\forall x \in \left( { - {\pi \over 2},{\pi \over 2}} \right)$$

$$\therefore$$ f is increasing on $$\left( { - {\pi \over 2},{\pi \over 2}} \right)$$

We know that strictly increasing function is one one.

$$\therefore$$ f is one one

$$\therefore$$ (b) is correct.

$$(\sec x + \tan x) = \tan \left( {{\pi \over 4} + {\pi \over 2}} \right)$$

as $$x \in \left( { - {\pi \over 2},{\pi \over 2}} \right)$$, then

$$0 < \tan \left( {{\pi \over 4} + {\pi \over 2}} \right) < \infty $$

$$0 < \sec x + \tan x < \infty $$

$$ \Rightarrow - \infty < \ln (\sec x + \tan x) < \infty $$

$$ - \infty < {[\ln (\sec x + \tan x)]^3} < \infty $$

$$ \Rightarrow - \infty < f(x) < \infty $$

Range of f(x) is R and thus f(x) is an onto function.

$$\therefore$$ (c) is correct.
3

JEE Advanced 2014 Paper 1 Offline

MCQ (More than One Correct Answer)
For every pair of continuous function f, g : [0, 1] $$\to$$ R such that max {f(x) : x $$\in$$ [0, 1]} = max {g(x) : x $$\in$$ [0, 1]}. The correct statement(s) is (are)
A
[f(c)]2 + 3f(c) = [g(c)]2 + 3g(c) for some c $$\in$$ [0, 1]
B
[f(c)]2 + f(c) = [g(c)]2 + 3g(c) for some c $$\in$$ [0, 1]
C
[f(c)]2 + 3f(c) = [g(c)]2 + g(c) for some c $$\in$$ [0, 1]
D
[f(c)]2 = [g(c)]2 + 3g(c) for some c $$\in$$ [0, 1]

Explanation

Suppose f(x) is maximum at c1 and g(x) is maximum at c2. When f(x) is maximum g(x) may or may not be maximum.


Therefore, in the function h(x) = f(x) $$-$$ g(x), we get

$$h({c_1}) = f({c_1}) - g({c_1}) \ge 0$$ and $$h({c_2}) = f({c_2}) - g({c_2}) \ge 0$$.

Therefore, h(x) = 0 for some c $$\in$$ [0, 1].


Therefore, $$h(c) = 0 \Rightarrow f(c) - g(c) = 0$$.

Therefore, $$f(c) = g(c)$$.

Option (a) $$ \Rightarrow {f^2}(c) - {g^2}(c) + 3[f(c) - g(c)] = 0$$ which is true from Eq. (i).

Option (d) $$ \Rightarrow {f^2}(c) - {g^2}(c) = 0$$ which is true from Eq. (i)

Now, if we take

f(x) = 1 and g(x) = 1, $$\forall$$x $$\in$$[0, 1]

Option (b) and (c) does not hold. Hence, option (a) and (d) are correct.
4

IIT-JEE 2012 Paper 2 Offline

MCQ (More than One Correct Answer)

Let $$f:( - 1,1) \to R$$ be such that $$f(\cos 4\theta ) = {2 \over {2 - {{\sec }^2}\theta }}$$ for $$\theta \in \left( {0,{\pi \over 4}} \right) \cup \left( {{\pi \over 4},{\pi \over 2}} \right)$$. Then the value(s) of $$f\left( {{1 \over 3}} \right)$$ is(are)

A
$$1 - \sqrt {{3 \over 2}} $$
B
$$1 + \sqrt {{3 \over 2}} $$
C
$$1 - \sqrt {{2 \over 3}} $$
D
$$1 + \sqrt {{2 \over 3}} $$

Explanation

$$f(\cos 4\theta ) = {2 \over {2 - {{\sec }^2}\theta }}$$

Let $$\cos 4\theta = t$$

$$ \Rightarrow 2{\cos ^2}2\theta - 1 = t \Rightarrow {\cos ^2}2\theta = {2 \over 3}$$

For $$t = {1 \over 3}$$ we have $${\cos ^2}2\theta = {2 \over 3}$$

$$\cos 2\theta = \sqrt {{2 \over 3}} $$ or $$\cos 2\theta = - \sqrt {{2 \over 3}} $$

$$f(\cos 4\theta ) = {2 \over {2 - {1 \over {{{\cos }^2}\theta }}}} = {{2{{\cos }^2}\theta } \over {2{{\cos }^2}\theta - 1}} = {{1 + \cos 2\theta } \over {\cos 2\theta }} = 1 + {1 \over {\cos 2\theta }}$$

Hence, $$f\left( {{1 \over 3}} \right) = 1 + \sqrt {{3 \over 2}} $$ or $$1 - \sqrt {{3 \over 2}} $$

Joint Entrance Examination

JEE Main JEE Advanced WB JEE

Graduate Aptitude Test in Engineering

GATE CSE GATE ECE GATE EE GATE ME GATE CE GATE PI GATE IN

Medical

NEET

CBSE

Class 12